Metaphysics - Ando, Takatura. author. aut Link
125 p.
Keywords: In the summer of I960 I visited Oxford and stayed there several months. This book was written as some slight memorial of my days in that ancient seat of learning. It is my pleasant duty to acknowledge the great debt I own to Mr. D. Lyness in the task of putting it into English. In addition I remember with gratitude Dr. J. L. Ackrill of Brasenose College, who gave me unfailing encouragement, and also Dr. R. A. Rees of Jesus College, who read my manuscript through and subjected it to a minute revision. Lastly for permission to quote from Sir W. D. Ross' translation of Aristotle's Metaphysics, I have to thank the editors of Oxford University Press. T.A. Kyoto, Japan Sep. I961. CONTENTS INTRODUCTION I I. THE ORIGIN OF THE CONCEPT OF METAPHYSICS 1. Reimer's Theory 3 2. Aristotle's Metaphysics 6 II. THE TRADITION OF THE CONCEPT OF METAPHYSICS I. Ancient Interpretations 17 Arabian School 20 2.